Osbeckia yercaudensis (Melastomataceae) a new species from the Eastern Ghats, India - Saravanan, Thokuluva Santharam; Kaliamoorthy, Seventhilingam (Phytotaxa, 2023)
A new species of Melastomataceae, Osbeckia yercaudensis, endemic to south India, is described from Shevaroy Hills, Tamil Nadu, India. It is morphologically allied to Osbeckia mehrana Giri & Nayar (1986: 429) and Osbeckia wightiana Bentham ex Wight & Arnott (1834:323), an endemic species from south India, but differs in the height of the plant, size of the leaves, 2–3-flowered cymes, oblong to slightly falcate sepals with irregularly emarginate apex and cochleate or U shaped, margins minutely toothed seeds. A detailed description, photographic illustration and comparison table are provided to facilitate identification.